Analysis of Competency and Work Discipline on Promotion With Work Motivation as An Intervening Variable at The National Narcotics Agency of North Sumatra Province - Ari Sujarno; Elfitra Desy Surya; Hernawaty Hernawaty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Promotion is a strategic aspect of human resource management in government organizations, including the North Sumatra Provincial National Narcotics Agency (BNNP Sumut), which has a crucial role in combating and preventing drug abuse. This study aims to analyze the effect of competence and work discipline on promotion with work motivation as an intervening variable at BNNP North Sumatra. This study uses a quantitative approach with a survey method. The population and sample of the study are all 84 permanent employees of BNNP North Sumatra. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of the SmartPLS application. The results show that competence and work discipline have a positive and significant effect on work motivation. In addition, competence and work discipline also have a positive and significant effect on job promotion. Work motivation is proven to have a positive and significant effect on job promotion. The results of the indirect effect test show that work motivation can significantly mediate the effect of competence and work discipline on job promotion. The coefficient of determination value shows that competence, work discipline, and work motivation can explain 60% of the variation in job promotion. The findings of this study indicate that objective and effective promotion at the North Sumatra BNNP can be achieved by strengthening employee competence, improving work discipline, and managing work motivation in a sustainable manner. The results of this study are expected to be taken into consideration by leaders in formulating transparent, fair, and merit-based career development policies.